Biosensors for the early diagnosis of acute myocardial infarction - Mendonça, Diogo Pinto Cardoso Mirandela de (2014)
Acute Myocardial Infarction (AMI) is the leading cause of death and disability in industrialized countries and is expected to become so in emerging countries by 2020. AMI is one of the main diseases with the highest rate of misdiagnosis. Of the majority of patients that arrive to the Emergency Department (ED) with cardiac pain and other symptoms suggestive of myocardial infarction, only a small portion actually may experience an Acute Myocardial Infarction. Therefore, diagnosing Acute Myocardial Infarction within such a large proportion of patients with cardiac pain is indeed a diagnostic challenge. For the correct diagnosis, it is essential to collect blood samples from the patient for the measurement of cardiac biomarkers, namely cardiac troponin I and cardiac troponin T. In this thesis, it is proposed a new type of biosensor for the early and reliable diagnosis of Acute Myocardial Infarction based on the use of metallic nanoparticles attached with aptamers as new Surface Enhanced Raman Scattering (SERS) platforms for the specific detection of cardiac troponin-I. Firstly, gold and silver colloidal nanoparticles (NPs) were synthesized via the classical citrate reduction method and later characterized to assess the quality of the substrate. Larger gold nanoparticles (AuNPs) with sizes ranging from 35-96 nm were also prepared by a seed-mediated growth method. The detection of cardiac troponin I proceeded with the addition of the protein at lower concentrations to the metallic colloids. The final results showed that AuNPs with larger sizes are good candidates to be used as SERS platforms for the detection of cardiac troponin I, because they have presented the highest enhancement of the Raman signals of the protein. These experiments have shown that larger AuNPs are definitely most suitable for this kind of applications. Peak bands were found to be attributed from characteristic bands present in proteins.